Clinical case of acute equine piroplasmosis in a Malaysian mare. - Al-Obaidi QT; Imad Ibrahim Ali Al-Sultan; Mohd Mokhtar Bin Arshad; Mohd Azam Khan Goriman Khan; Mimi Armiladiana Binti Mohamad (2015)
This is the first clinical report on acute piroplasmosis in a mare in Malaysia. A 20 years old local thoroughbred mare showed clinical signs of acute equine piroplasmosis, anaemia, increase in erythrocytes sedimentation rate (ESR) and reticulocytosis, neutrophilia and lymphocytosis, increase in aspartate amino transferase (AST), alanine amino transferase (ALT), alkaline phosphatase (ALKP), blood urea nitrogen (BUN) and total bilirubin and decreased total protein (albumins and globulins), calcium, phosphorous, glucose and creatinine. Microscopic examination of blood smear was positive for Theileria equi and Babesia caballi. Competitive ELISA test was confirmative to antibodies of T. equi and B. caballi. Multiplex PCR test was positive for the causative agents of equine piroplasmosis. Microscopic localization of micro and macroschizontes in the cytoplasm of lymphocytes and macrophages in various organs provided a distinct hisopathological evidence of acute form of the disease.